CITYSCAPE OF MEDIEVAL PATNA: CONTINUITY AND CHANGE: Exploring the Historical and Cultural Transformations of Medieval Patna (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The city of Patna has a long history dating back from 6th century BC to the present time. The article not only looks at the evolution of Patna as an urban centre but focusses on the continuity and change over the period of time. Patna’s administrative and economic significance is very well reflected in its varied activities during the period under review. What remained unchanged since its inception was the cosmopolitan environment and composite culture.